Current consensus on clinical features, pathogenesis, diagnosis and management of autism spectrum disorder in children: A brief review - Dr Prateek Kumar Panda (Pediatric Review: International Journal of Pediatric Research, 2019)
Autism spectrum disorder (ASD) usually presents in early developmental period, in children less than five years usually with poor social relations, verbal and nonverbal communications and stereotypic and repetitive behavior. The prevalence of ASD is increasing rapidly; especially in urban community of developed as well as developing nations.Combined interaction of genetic and environmental factors has been proposed as the possible neuropathogenetic mechanism underlying ASD. Children with ASD have specific abnormalities in functional connectivity of brain and altered fecal microbiota. Children with Fragile X syndrome, Rett syndrome and Tuberous sclerosis often have autistic features.Interviewing the caregiver and observation of the child is the only definitive way to confirm the diagnosis of ASD. Recently DSM V criteria have combined under a single umbrella all the autistic disorders including Asperger syndrome and pervasive developmental disorder-not otherwise satisfied. Apart from DSM V criteria, Autism Diagnostic Observation Schedule (ADOS) and Childhood Autism Rating Scale (CARS) are also useful in diagnosis and evaluation of children with ASD. Autistic children are more likely to have hyperactivity, inattention, sleep abnormalities and epilepsy, as compared to general population. Applied behavioral analysis, sensory integration therapy and structured teaching are used in the management of autism spectrum disorder, along with atypical antipsychotics like Risperidone and Aripiprazole. Various complementary and alternative treatments like music therapy, oral probiotics and gluten free, casein free diet are currently under evaluation in various clinical studies.